173k views
3 votes
2. Find the product of (x+1)(x^2-3x+7)

User Tometzky
by
6.0k points

2 Answers

4 votes

Answer:

x

2

+

3

x

7

=

0

Add

7

to both sides of the equation.

x

2

+

3

x

=

7

To create a trinomial square on the left side of the equation, find a value that is equal to the square of half of

b

.

(

b

2

)

2

=

Add

7

to both sides of the equation.

x

2

+

3

x

=

7(

3

2

)

2

Add the term to each side of the equation.

x

2

+

3

x

+

(

3

2

)

2

=

7

+

(

3

2

)

2

Simplify the equation.

Tap for more steps...

x

2

+

3

x

+

9

4

=

37

4

Factor the perfect trinomial square into

(

x

+

3

2

)

2

.

(

x

+

3

2

)

2

=

37

4

Solve the equation for

x

.

Tap for more steps...

x

=

±

37

2

3

2

The result can be shown in multiple forms.

Exact Form:

x

=

±

37

2

3

2

Decimal Form:

x

=

1.5413812

,

4.54138126

Explanation:

User ModusCell
by
5.8k points
1 vote

Answer:x^3-2x^2+4x+7

Explanation:

User Hasintha Janka
by
6.2k points